1999
DOI: 10.1364/josab.16.000662
|View full text |Cite
|
Sign up to set email alerts
|

Theory of ultrabroadband optical pulse generation by induced phase modulation in a gas-filled hollow waveguide

Abstract: Generation of an ultrabroadband optical pulse with a fluent frequency dependency of the phase is important for creating a monocyclelike optical pulse and for shaping multiwavelength optical pulses. A previously proposed method that uses induced phase modulation between a femtosecond fundamental wave 1 and its second-harmonic wave 2 ϭ 2 1 in a fused-silica fiber is applied to a capillary fiber filled with noble gas. Analytic results of chirps without dispersion but with loss in the fiber are shown, and the opti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

2000
2000
2001
2001

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 17 publications
3
13
0
Order By: Relevance
“…Converting the units of to [watt ] by multiplying and using the relations and , where is the linear index of refraction of the medium, we have (6) where (7) Taking the inverse Fourier transform of (6), we have (8) where…”
Section: Nonlinear Optical Pulse Propagation Equationsmentioning
confidence: 99%
See 3 more Smart Citations
“…Converting the units of to [watt ] by multiplying and using the relations and , where is the linear index of refraction of the medium, we have (6) where (7) Taking the inverse Fourier transform of (6), we have (8) where…”
Section: Nonlinear Optical Pulse Propagation Equationsmentioning
confidence: 99%
“…In the SVEA, we neglect the term in (6). Also, it is assumed that in (6) In addition to the assumptions and is conventionally assumed in the SVEA.…”
Section: A the Svea Equationmentioning
confidence: 99%
See 2 more Smart Citations
“…We have analyzed nonlinear chirp from SPM and IPM in the case of two-pulse propagation in a single-mode capillary fiber and found that by choice of a proper delay time between pulses it is possible to generate ultrabroadband pulses whose spectrum covers the near infrared to the near ultraviolet, with a f luent frequency dependence of the phase by means of a practical setup. 9 Since the second-harmonic and the fundamental waves are generated from one common femtosecond pulse, the carrier-phase difference between their waves is constant. 10,11 This enables us to synthesize constructively two spectrally broadened waves at the fiber output.…”
mentioning
confidence: 99%